Electroacupuncture as adjunctive therapy for insomnia via targeting the GABAergic microbiota-gut-brain axis: a mini review - Wang, Xiao; Yan, Lijuan; Zhang, Xiaodong; Liu, Xiang; Yang, Bin (Frontiers in Psychiatry, 2025)
Insomnia, affecting up to 30% of adults (typically 18–65 years), is characterized by GABAergic dysfunction and hyperarousal. This mini-review establishes three pivotal advances in insomnia therapeutics: Firstly, it is demonstrated that microbiota-gut-brain axis (MGBA) dysregulation is mechanistically central to insomnia, directly linking gut dysbiosis to vagal, hypothalamic-pituitary-adrenal (HPA), and γ-aminobutyric acid (GABA) axis dysfunction and neuroinflammation. Secondly, the present study documents the unique multitarget effects of electroacupuncture (EA), which have been shown to simultaneously normalize HPA axis activity, enrich GABA-producing microbiota, improve the vagal tone, and suppress neuroimmune activation. The aforementioned effects collectively resolve insomnia’s multifactorial etiology. Thirdly, clinical evidence confirms the sustained efficacy of EA to be comparable to that of hypnotics, yet with superior safety and durability. EA redefines therapeutic frameworks by integrating biological and neural interventions that are inaccessible to single-target approaches.